Internal migration in the United States - Raven Molloy; Christopher L. Smith; Abigail Wozniak (Institute for the Study of Labor (IZA), 2011)
We review patterns in migration within the US over the past thirty years. Internal migration has fallen noticeably since the 1980s, reversing increases from earlier in the century. The decline in migration has been widespread across demographic and socioeconomic groups, as well as for moves of all distances. Although a convincing explanation for the secular decline in migration remains elusive and requires further research, we find only limited roles for the housing market contraction and the economic recession in reducing migration recently. Despite its downward trend, migration within the US remains higher than that within most other developed countries.
urn:nbn:de:101:1-201108152107
Keywords: J61; R23; J1; 330; internal migration; migration trends; housing crisis; U.S. recession; cross-country comparisons